Kintanti kinų tapatybė globalėjančiame pasaulyje - Smith (Xu, Robert Paul Paul; Shu), Ke (Information & Media, 2008)
Visuotiniame pasaulyje kinta kultūrinis žemėlapis. Greita ekonomikos plėtra skatina kinų kultūros pokyčius. Jaunimui būdingas individualumas, silpni giminystės ryšiai, meilės, sekso ir vedybų politikos pokyčiai. Dėl gimimų skaičiaus ribojimo Kinijoje vaikai ir jaunimas labiau linkę būti individualistai nei kolektyviški, tai skatinama ir per filmus ar televizijos serialus. Dažniau jie galvoja apie save nei apie Jus ar Juos. Giminystės ryšiai Kinijoje taip pat silpni, todėl šiame darbe daroma prielaida, kad būtent dėl tokių priežasčių 2006 m. labai padaugėjo santuokų su užsieniečiais. Taip pat tai atsiliepia ir vertinant požiūrį į partnerį. Kaip teigia pranešimo autorius, tai turi įtakos ir santuokai, seksualiniams santykiams. Chinese changing identities in globalised world Robert Paul Smith (Xu, Ke Shu) Summary The cultural map is changing in the globalised world. The quickly developing economy changes the identities of Chinese quietly. Typically, the young generation is more individualistic, the traditional kinship weakens, and the ideology on love, sex and marriage changes. Because of Chinese birth control policy, the children and young people who grow up as the only child in her or his family respect individualism more than collectivism influenced by movies of Hollywood and Western TV soap plays. What they think most is in terms of “I”, not “you” or “they”. Kinship in China is now much weaker in Mainland China than it was in the past. In fact, there are many empty-nest families, in which children have left home to seek success in metropolis in China and cities in Foreign Countries, and their old, sick parents are suffering in loneliness. In the Chinese countryside, a lot of young couples refuse to support their old parents. Some old parents are even driven out and suffer from hunger. Now in China, DINK marriages and sexless marriages are common in the cities. More than 400,000 Chinese people have married foreigners till 2006. In 2005, more than 70,000 Japanese men and 41,000 Korean men have married Chinese women. Rich men change girlfriends or sex partners frequently. Some even keep special, private houses where their girlfriends live apart from their wives. Thousands of workers, drawn from farms to jobs in the cities, are sexually hungry and visit illegal striptease shows frequently. The new generation of Chinese people does not even value virginity very highly. There are too many quick marriages in China now. This was especially true in the lucky wedding year of 2006. Some married quickly and divorced very soon. Key words: change, identities, individualization, kinship, love n>